(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The Armenian relationship with the Abbasid state constitutes an important and extensive study in history. The Armenian relationship with the Abbasid state used to vary between reconciliation and rebellion against the Abbasid authority. Sometimes the Armenians were on the side of the Abbasids against Byzantium, and at other times they did the opposite. The Abbasid authorities, where the Armenians participated and supported the rebels against the Abbasid state in many cases, because of their desire to obtain independence. Especially in the fields of military and political relations, given the important strategic location of Armenia. This position prompted both the Arab, Muslim and Byzantine parties to try to win over the Armenians to his side, because of the Armenians’ influence in the course of events, and the relations of the Armenians with these two parties were oscillating between support and submission, and between revolution and uprising.